Effect of the SADIVA Digital Application on Knowledge, Counseling, and Screening Skills of Health Cadres for Early Breast and Cervical Cancer Detection: A Quasi-Experimental Study - Syajaratuddur Faiqah; Fitra Arsy Nurcory’ah; Mutiara Rachmawati Suseno; Endah Wijayanti (Direktorat Politeknik Kesehatan Makassar, 2026)
Breast cancer and cervical cancer are among the most common cancers affecting women. Health cadres play an important role in encouraging women to undergo visual inspection with acetic acid (VIA) and clinical breast examination (CBE) at healthcare facilities. The “SADIVA” app was developed as an educational tool to assist health cadres in promoting awareness about the early detection of breast and cervical cancer. This study aimed to determine the effect of the “SADIVA” digital media on improving the knowledge, counseling skills and screening skills of health cadres in conducting education and early detection for breast and cervical cancer among women of reproductive age. This study used a Two Group Pretest-Posttest design. The population included health cadres working in the jurisdiction of the Sesela Community Health Center. A total of 60 participants were selected through purposive sampling and divided into two groups, consisting of 30 participants in the intervention group and 30 participants in the control group. The intervention was conducted for four weeks. The intervention group received training on how to use the SADIVA app, while the control group received a booklet. The training was conducted for approximately 60 minutes. Following the training session, all respondents carried out independent practice at least three times per week and were monitored using a checklist and a WhatsApp group. The results of the Mann–Whitney test for the knowledge variable in the post-test showed a Z-score of -2.317, a p-value of 0.016 (p < 0.05), and an effect size of 0.30. Meanwhile, the screening skills variable demonstrated a Z-value of -6.318, a p-value of < 0.001 (p < 0.05), and an effect size of 0.82. And for the health education skills variable, a Z-value of -3.508 was obtained; p-value < 0.001 (p < 0.05); with an effect size of 0.46. Thus, it can be concluded that there are significant differences in the post-test scores for knowledge, screening skills, and counseling skills between the intervention group and the control group, with the effect sizes for each variable being moderate for the knowledge and counseling skills variables, and having a large effect on the improvement in the respondents’ screening skills. The “SADIVA” digital media significantly enhanced the knowledge, counseling abilities, and screening skills of health cadres in supporting the early detection of breast and cervical cancer among women of reproductive age.